Investigating the Causal Association Between Plasma Lipids and the Risk of Squamous Cervical Cancer: A Two-Sample Mendelian Randomization Study: Plasma Lipids and Squamous Cervical Cancer: A Mendelian Study - Cui, Yuemei; Li, Ya; Na, Jing; Lu, Junling; Wang, Xinyou; Han, Shichao; Wang, Jun (Journal of Medical Biochemistry, 2025)
Purpose: This study aimed to investigate the causal relationship between plasma lipid levels—total cholesterol (TC), triglycerides (TGs), low-density lipoprotein cholesterol (LDL-C), and high-density lipoprotein cholesterol (HDL-C)—and the risk of squamous cervical cancer (SCC) using Mendelian Randomization (MR).Materials and Method: Genome-wide association study (GWAS) data for plasma lipid traits were obtained from the Global Lipids Genetics Consortium (GLGC), and SCC outcome data were sourced from the FinnGen consortium. The primary analysis was conducted using the inverse variance weighted (IVW) method, supported by MR-Egger regression, weighted median, and weighted mode approaches. Sensitivity analyses were performed to assess the robustness of the results, and the Steiger test was used to evaluate the directionality of the associations.Results: The IVW analysis revealed that higher plasma levels of TC (OR: 1.777; 95% CI: 1.118–2.825; p = 0.015) and LDL-C (OR: 1.674; 95% CI: 1.013–2.767; p = 0.044) were associated with an increased risk of SCC. No significant associations were found between TGs (OR: 0.644; 95% CI: 0.343–1.212; p = 0.173) or HDL-C (OR: 1.050; 95% CI: 0.616–1.790; p = 0.857) and SCC.Conclusions: This study provides evidence of a causal relationship between elevated plasma TC and LDL-C levels and a higher risk of SCC, highlighting a novel aspect of SCC etiology. These findings may inform further functional and clinical research in the progression of SCC.